Science Literacy and Its Impact on Scientific Knowledge Acquisition: A Review of Current Research and Practices - Saad, Rezkawati; Nurlina, Nurlina; Bancong, Hartono (PPSDP International Journal of Education, 2025)
This bibliometric and thematic review synthesizes global research on science literacy and its influence on scientific knowledge acquisition from 2016 to 2025. Drawing on 1,171 Scopus-indexed documents (articles, conference papers, and book chapters), the study employs co-word analysis (keyword co-occurrence), co-authorship analysis, and thematic evolution mapping using VOSviewer and Biblioshiny to examine publication trends, influential contributors, collaboration patterns, and evolving themes. The analysis demonstrates a steady rise in publications, especially after 2020, signaling intensified scholarly attention to science literacy in addressing global challenges such as health crises, climate change, and technological transformation. Keyword networks and thematic evolution further indicate a conceptual shift from treating science literacy mainly as an educational outcome to framing it as a multidimensional construct integrating cognitive, social, digital, and ethical dimensions. The United States, China, and Indonesia emerge as major contributors, alongside expanding international collaboration and diversified research contexts. Core themes scientific literacy, education, and students now connect strongly with emerging topics including health literacy, digital literacy, and citizen science. Overall, these results highlight science literacy’s crucial role in supporting inquiry-based learning, informed citizenship, and sustainable development, while also identifying dominant trends, research gaps, and implications for inclusive, evidence-based science education worldwide.